2013
DOI: 10.1016/j.jom.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The relative impact of attribute, severity, and timing of psychological contract breach on behavioral and attitudinal outcomes

Abstract: A psychological contract defines the perceived reciprocal obligations that characterize a relationship between an individual and organizational entity. Breach of a psychological contract can negatively affect work behaviors and attitudinal perceptions, and may also elicit an emotional response (violation) which can help to explain these negative consequences. This research focuses on the role of psychological contracts in a supply chain setting. We explore when and how three conditions of psychological contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 106 publications
(152 citation statements)
references
References 84 publications
(107 reference statements)
7
144
1
Order By: Relevance
“…Finally, although the use of undergraduate students for experimental research is sometimes questioned, we posit that our theoretical framework includes students within its boundary scope conditions, and that the coursework completed by each student and the training provided to them during the experiment further establishes suitability of the sample (Thomas, ). Moreover, this experiment was conducted with a group of MBA students, and revealed substantively similar results as those conducted with undergraduate students (Eckerd et al., ). This provides a level of confidence in our interpretations regarding the relationships under investigation (Stevens, ).…”
Section: Limitations and Future Research Directionssupporting
confidence: 76%
See 3 more Smart Citations
“…Finally, although the use of undergraduate students for experimental research is sometimes questioned, we posit that our theoretical framework includes students within its boundary scope conditions, and that the coursework completed by each student and the training provided to them during the experiment further establishes suitability of the sample (Thomas, ). Moreover, this experiment was conducted with a group of MBA students, and revealed substantively similar results as those conducted with undergraduate students (Eckerd et al., ). This provides a level of confidence in our interpretations regarding the relationships under investigation (Stevens, ).…”
Section: Limitations and Future Research Directionssupporting
confidence: 76%
“…In Eckerd et al. 's () previous evaluation of post‐breach order quantities, they find that orders trend lower than what would otherwise be mathematically predicted due to reneging and breaches of major severity. However, given that their study evaluates only the orders occurring post ‐breach, we include here hypotheses regarding decision making behavior in the periods during the breach.…”
Section: Theoretical Developmentmentioning
confidence: 89%
See 2 more Smart Citations
“…Based on the analysis of 300 doctors and nurses in Pakistan, Ahmed et al (2013) found that PCB had a significantly positive direct effect on doctors’ and nurses’ CWBs. When perceiving PCB, employees may become angry and frustrated (Eckerd et al, 2013). These negative emotions can elicit employees’ CWB (Fox and Spector, 2002; Penney and Spector, 2005).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%